(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
Raspberry leaf blotch emaravirus (RLBV) has become established in many Serbian raspberry orchards as the most prevalent virus of raspberries in the country. The aim of this study was to evaluate the impact of RLBV on the red raspberry ‘Willamette’ variety. A trial was conducted in four raspberry orchards located in Western Serbia. Fruits from RLBVinfected and uninfected canes were analyzed for fruit size (fruit length, width, height, shape, and weight), soluble solids content, pH, titratable acidity, total sugars, and total phenolic and anthocyanin contents. The results of the study confirmed that RLBV significantly decreases fruit size and weight (9.15-27.49%) of ‘Willamette’ fruits. Soluble solids content was higher in infected fruits (1.55-7.39%), but the increase was not significant. RLBV did not cause significant changes in titratable acidity of raspberry juice, pH or total sugars content. Total phenolic and anthocyanin contents were higher in fruits of RLBV-infected plants in two out of four locations.